Komunikasi Transedental Dalam Kidung Jawa - Soraya, Serin Himatus (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2022)
This paper aims to describe the communication between humans and God contained in Javanese songs. This song is believed to be a prayer that is a fusion of self-protection from various dangers that may occur. However, many also think that this song is a form of polytheism or associating partners with Allah SWT. Using a descriptive qualitative method, this study attempts to describe the text and context of the Song of Rumekso Ing Wengi regarding the relationship between human s and God. The results of this study found that the meaning of the content in these songs is similar to that of Surahs An - Nas and Al-Falaq, namely requests for help from Allah SWT as the One who controls thenight to avoid the evils of fellow humans or other creatures. This shows that humans and God have atranscendental relationship that cannot be ignored. Humans as weak creatures need God's help to saveor prevent themselves from the difficulties they may experience.